Comparison of Cultural Awareness in English Textbook for General and Elective Programs Used by EFL of Senior High School - Rismasari; Safnil Arsyad (Journal of English for Specific Purposes in Indonesia (JESPI), 2023)
The main goal of this research is to determine "What cultural awareness is represented in the English textbooks Pathway to English Grade X General Programme?”, “What cultural awareness is represented in the English textbooks Pathway to English Grade X Elective Programme?”, and “What are the comparison between two English textbooks?”. Two English textbooks from the same author and publisher but used in different programmes for senior high school were chosen for this study, they are Pathway to English Grade X, General Programme; and Pathway to English Grade X, Elective Programme. This study is part of the qualitative approach to library research. To make it easier to understand, Percentage-based quantitative analysis is used. Researchers collect data from English textbooks in the context of textbook analysis to come clean about the way culture awareness contents are represented in two English textbooks. The findings show that all English textbooks presented cultural awareness content, and the cultural awareness contents in each English textbook used by Senior High School as EFL have covered four aspects of cultural content for Book I, and seven aspects of cultural content for Book II. Although not all aspects of the cultural category are covered in the English textbook, it is clear that the cultural content exceeds half of the total. The percentage of those is as follows: Book I have 72,80 per cent and Book II have 70 per cent. This suggests that the authors should use several different cultural awareness aspects in their English textbook as EFL.